Construction of frustrated Lewis pairs at N and Mo2C double sites boosts efficient electrocatalysts for Li-S batteries. (2nd November 2022) - Gu, Rong; Zhang, HaiYan; Geng, Yuan; Zhu, Sheng; Xu, QunJie; Min, YuLin
Highlights: The uniformly dispersed N element promotes the dispersion of Mo2 C nanoparticles. The Mo2 C site adjacent to N forms a spatially frustrated Lewis pairs with it. It has an initial specific capacity of 1186 mAh g −1 at 1C. Abstract: The polysulfide shuttle effect and uncontrollable Li-dendrite growth on Li anode are the major reasons limiting the commercial development of Li-S batteries. Transition metal compounds on the carbon vector on the transition of polysulfides have been widely reported. However, there are few reports on the principle of simultaneous transformation and the effect of double active site spacing. Herein, we are based on the mechanism of the anchoring effect of doped elements on the carbon vector. Molybdenum carbide nanoparticles are mounted onto N-doped carbon nanosheets and coated on commercial separators (Mo2 C-NCNS) for modification to satisfy the synchronization of S cathode and Li anode. The uniformly dispersed N element promotes the dispersion, homogenization and micro size regulation of Mo2 C nanoparticles by anchoring Mo atoms. At the same time, the Mo2 C site adjacent to N forms a spatially frustrated Lewis pairs with it. The reasonable spacing between them promotes the uniform deposition of lithium ions, the rapid transformation of polysulfides and the synchronous synergy between them. Characterization by XPS showed that using carbon as a bridge site further enhanced the strong metal-vector interaction between C3 N4 and Mo2 C, so as to improve the reaction kinetics. Thus, it has an initial specific capacity of 1186 mAh g −1 at 1C, and after 1000 cycles, 400 mAh g −1 remained, with a decay rate of only 0.06% per cycle. At a current density of 1 mA/cm 2, the symmetric cell with Mo2 C-NCNS modified separator exhibits steady cyclability over 1500 h, with a small overpotential of 76 mV.